PELAKSANAAN UU NO. 18 TAHUN 2019 DI KECAMATAN PACET KABUPATEN MOJOKERTO - Safitri Damayanti, Anis; Muhaimin, Hikmah; Suprapto (Universitas Islam Majapahit, Indonesia, 2022)
Law Number 18 of 2019 concerning Islamic Boarding Schools was passed by the People's Representative Council of the Republic of Indonesia (DPR RI) in10th plenary meeting, September 24 2019. This law is a manifestation of the Indonesian state's efforts to regulate Islamic boarding schools for the purpose ofcreating shared justice, in line with the values of Pancasila. With the passing of this law, Islamic boarding schools received affirmation,legal recognition, and better facilitation, accelerate their growth and development. This law is part ofpublic policy to improve Islamic boarding school development towards a better direction, in accordance with the state's goal of educating the nation.Islamic boarding schools, as Islamic educational institutions, have an important role in spreading and developing the teachings of the Islamic religion, whileadapting to current developments by adding a general knowledge curriculum. Along with development, there are twotypes of Islamic boarding schools, namely modern and traditional, each with its own characteristics. Amanatul Ummah Islamic Boarding School is one of themeducational institutions that are under the influence of Law Number 18 of 2019, which has experienced rapid development withproviding quality education, both in religious and general aspects. With this law, it is hoped that the rights of the students will be guaranteedand Islamic boarding school caregivers are increasingly guaranteed, and the implementation of this law can run well to achieve educational goalsbetter.